Síntese e caracterização de estruturas anódicas com condutividade elétrica mista, iônica e eletrônica, para célula a combustível de óxido sólido - Silva, Eduardo da Rosa (2020)
Solid oxide fuel cells are equipment that have great potential for the generation of electric energy, however, new materials need to be studied for application as an anode, aiming at fuel flexibility and performance increase. The main objective of this thesis was to investigate the possibility of applying a material composed of yttrium doped strontium titanate for such application. The material was synthesized with a concentration of 0%, 4% and 8% of dopant, calcined and sintered in an atmosphere of Ar (Argon) and Ar + 5% H2. Only materials calcined in an atmosphere of Ar + 5% H2 presented a satisfactory crystallinity and purity. Of these, the structure consisting of 8% Y showed a formation of a secondary phase of pyrochlore. In the sintering step, the reducing atmosphere favored the electronic conduction phenomena, as it formed a structure with more circular and homogeneous grains. However, the secondary phase of pyrochlore, since it has an insulating character, decreased the total electrical conductivity, however, it increased considerably the density of capacitance because it has a structure with a higher concentration of interfaces between grain/grain and grain/secondary phase. From impedance spectroscopy analysis it was possible to separate the resistances from the grain bulk and grains boundaries, the latter proved to be greater than the first, with a greater increase for the sample with the secondary phase of pyrochlore.